ANALISIS TINGKAT KECERDASAN EMOSIONAL MAHASISWA S1 PENDIDIKAN BUDHHA ANAK USIA DINI SEBAGAI CALON GURU PAUD - Astri Chintya Astana (Jurnal Citra Pendidikan, 2026)
This study aims to analyze the emotional intelligence of students training to become Early Childhood Education (ECE) teachers and its implications for developing professional competence. The study used a descriptive quantitative approach with 50 students from Institut Nalanda as participants. Data were collected through a questionnaire measuring five aspects of emotional intelligence: self-awareness, self-regulation, motivation, empathy, and social skills. The results show that, overall, the students’ emotional intelligence is at a medium to high level, with 54% in the medium category and 36% in the high category. Self-awareness had the highest average score, while motivation had the lowest. This suggests that students are relatively good at recognizing and understanding their own emotions but still need to improve their ability to motivate themselves. Overall, emotional intelligence plays an important role in supporting students’ interaction skills, emotion management, and readiness for teaching practice. The study implies that strengthening emotional intelligence should be integrated into the education of future teachers through learning, training, and practical field experiences to better develop their professional competence.